2019
DOI: 10.1016/j.ica.2019.119066
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and investigation of a tris-cyclometalated iridium complex bearing a single quarternary ammonium group

Abstract: Synthesis and investigation of a tris-cyclometalated iridium complex bearing a single quarternary ammonium group.', Inorganica chimica acta., 497. p. 119066.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 25 publications
(38 reference statements)
0
4
0
Order By: Relevance
“…We have recently published a report on a quarternary ammonium salt of the butyl substituted complex, in addition to the previously mentioned report on the complexes bearing the butyl and dodecyl chain. [21][22] Our previously reported complexes have displayed lysosomal localization. However, the quarternary ammonium complex stood out in terms of its significantly lower cytotoxicity.…”
Section: Cellular Experimentsmentioning
confidence: 92%
See 1 more Smart Citation
“…We have recently published a report on a quarternary ammonium salt of the butyl substituted complex, in addition to the previously mentioned report on the complexes bearing the butyl and dodecyl chain. [21][22] Our previously reported complexes have displayed lysosomal localization. However, the quarternary ammonium complex stood out in terms of its significantly lower cytotoxicity.…”
Section: Cellular Experimentsmentioning
confidence: 92%
“…The first one was synthesized as a direct analogue of the previously reported complexes containing simple alkyl groups while the latter was synthesized with reduced cytotoxicities in mind as it was observed for complexes where the secondary amino group is transformed into its tertiary amino analogue or a quarternary ammonium group. [21][22] Figure 1. Structures of tris-cyclometalted aminoalkyl iridium complexes reported by our group.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the light-responsive rotaxane exhibits substantially increased cytotoxic activity upon continuous irradiation, resulting from the translocation of the platinum(II) salphen complex to the cell nucleus and its binding to DNA. Vaźquez, Vilar, and coworkers have developed dimeric platinum(II) salophen complexes linked with different peptide sequences (507) for targeting multimeric G-quadruplex DNA. 944 The peptide linker plays an important role in the binding affinity and selectivity of the complexes toward different G-quadruplex DNA topologies.…”
Section: Nucleic Acidsmentioning
confidence: 99%
“…Furthermore, a water-soluble iridium(III) complex carrying two morpholine units ( 275 ) has been developed for lysosome-targeted imaging and PDT . Kielar and co-workers have demonstrated that iridium(III) complexes containing a pH-sensitive aminoalkyl moiety ( 276 and 277 ) can also specifically target the lysosomes. …”
Section: Luminescent Transition Metal Complexes As Probes For Specifi...mentioning
confidence: 99%